SATIRE IN THE POETRY OF DHUMIL AND LAISHRAM SAMERENDRA - Devi, Wankhem Meratombi (ShodhKosh: Journal of Visual and Performing Arts, 2023)
Dhumil is a famous poet of contemporary Hindi poetry. His magic is clearly visible in the world of poetry. His feelings and thoughts are amazing. He has presented different forms of man in a different way. Dhumil has openly expressed the feelings of man. He said what he got in life. He has closely observed the things around him and made them the soul of poetry. Portraying the life of the common people can be considered the main theme of his poetry. Dhumil wants to erase the difference between the poor and the rich, so he expresses the feeling of equality in his works. The words in his poetry reveal situations. Because his words are very powerful, he says what he wants to say, so Dhumil is considered the best poet in contemporary Hindi literature.